Temperature effects on summer growth rates in the Antarctic scallop, Adamussium colbecki - HEILMAYER O.; C. HONNEN; U. JACOB; T. BREY; CHIANTORE, MARIACHIARA; CATTANEO VIETTI, RICCARDO (2005)
Annual growth rates of Antarctic marine organisms are low compared to their relatives from warmer waters. Previous studies hypothesise that high food availability during austral spring–summer may enable Antarctic invertebrates to attain comparatively high short-term growth rates despite the low temperature. Neither a temperature-growth experiment with juvenile Adamussium colbecki (Smith 1902) nor the comparison of A. colbecki summer growth rates with an empirical scallop specific growth-to-temperature relationship could confirm this hypothesis. Hence, summer growth rates of young, immature A. colbecki are strongly affected by temperature, i.e. no ‘‘uncoupling’’ from temperature.